Nutritional Education and Its Effects on Household Food Insecurity in Southeastern Iran - Zinat Mortazavi; Ahmad Reza Dorosty; Mohammad Reza Eshraghian; Mohtasham Ghaffari; Alireza Ansari-Moghaddam (Tehran University of Medical Sciences, 2021)
Background: Food insecurity can affect health directly or indirectly through its impact on nutritional status. We aimed at determining the effects of nutrition education intervention on household food insecurity in Zahedan, southeast Iran. Methods: The study was conducted using multi-stage sampling method. The first stage was a cross-sectional investigation whereby 2,160 households were studied in Zahedan in 2015. The prevalence of food insecurity was determined and food-insecure households were identified. Household food security status was assessed through the 18-item US Household Food Security Survey Module. In the second stage, based on the determined sample size of 150 households in each group, eligible households were randomly divided into the intervention and control groups. Before the educational intervention, questionnaires including demographic and socioeconomic information were completed for both groups. Then, data analysis was performed and the intervention was conducted on the intervention group. Six months post-intervention, a final assessment was made by interviewing the two groups to complete demographic, socioeconomic, and household food security questionnaires. Results: The prevalence of food insecurity in the 2,160 households was 58.8%. After the intervention, the number of food-insecure households diminished by 22% in the intervention group, and these households were assigned to the food secure category. After controlling the confounding variables, the educational intervention was significantly effective in reducing food insecurity score (P<0.001). Conclusion: The findings demonstrated the beneficial role of nutritional education and the skills of resource management in modifying nutritional behaviors and improving food security in the study population.